Risk assessment of bitumen tanker operations using intuitionistic fuzzy fault tree analysis - Özdemir, Batur Alp (Graduate School, 2025)
This thesis focuses on the risk profile of bitumen tanker operations, which require specialized engineering solutions due to the high temperature requirements and viscous nature of the cargo. Transporting bitumen involves maintaining strict thermal parameters throughout the entire process, demanding a multidimensional assessment of technical, environmental, and human-related factors. In this context, the potential failure types that may occur during loading, navigation, and discharge operations onboard bitumen carriers have been analyzed through a systematic and structured approach. The challenges encountered in bitumen tanker operations are not limited to technical failures but can also lead to significant environmental consequences, safety hazards, and economic losses. For this reason, the study examines not only the root causes of mechanical failures but also the broader systemic implications, incorporating issues such as heat loss, line blockages, human errors, and procedural deviations into the analysis. Each operational phase of the tanker is modeled through interconnected fault chains and evaluated using an intuitionistic fuzzy logic structure to produce a more inclusive and realistic analysis. In this study, the Intuitionistic Fuzzy Fault Tree Analysis (IFFTA) method, known for its effectiveness in modeling uncertainty in complex decision environments, was employed. Unlike conventional fault tree analysis, IFFTA allows for the integration of expert intuition and partial judgments, offering a more flexible and inclusive framework for risk assessment. Supported by literature review, field observations, and expert interviews, the fault tree model was structured around top, intermediate, and basic event levels. The resulting fault tree represents each link in the operational chain of the bitumen tanker and enables a more accurate identification of root causes. The developed fault tree model includes 67 distinct basic events related to bitumen tanker operations. It was submitted to 10 domain experts with extensive field experience and niche technical knowledge. Each expert was asked to assess the relative importance of each event using a 7-level intuitionistic scale, structuring their evaluations according to the conventional understanding of risk as the product of frequency and severity. This methodology ensured that expert assessments were grounded in both intuition and technical logic. The fact that all consulted experts had direct, hands-on experience with bitumen tanker operations significantly enhanced the reliability and practical relevance of the collected data. The findings revealed that the most critical failures in bitumen tanker operations stem not primarily from technical breakdowns but from human factors and organizational deficiencies. Key issues included disruptions in thermal control, degraded insulation systems, insufficient preparedness for emergency scenarios, and inconsistent procedural compliance. Accordingly, strategic recommendations were developed focusing on personnel training, preventive maintenance planning, standard operating procedures, and the formulation of scenario-based emergency action plans. Additionally, elements such as vessel design, insulation efficiency, heating system reliability, and environmental safety were evaluated through a multi-dimensional risk matrix. The study emphasizes the necessity of addressing technical reliability and human performance as interdependent factors, aiming not only to analyze existing risks but also to promote a proactive safety culture in the bitumen transport industry. In conclusion, this thesis provides a comprehensive and practical risk assessment model that contributes to both academic literature and real-world maritime operations. The analysis offers valuable insights for maritime companies and stakeholders to develop safer and more efficient strategies for managing the complex challenges of bitumen tanker operations.
Bitüm tankeri operasyonlarında sezgisel bulanık hata ağacı analizi kullanılarak risk değerlendirilmesi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: fuzzy; bulanık; discharge systems; deşarj sistemleri; fault tree analysis; hata ağacı analizi